5-Substituted-N-pyridazinylbenzamides as potent and selective LRRK2 inhibitors: Improved brain unbound fraction enables efficacy. Issue 2 (15th January 2019) - Ding, Xiao; Stasi, Luigi Piero; Dai, Xuedong; Long, Kai; Peng, Cheng; Zhao, Baowei; Wang, Hailong; Sun, Changhui; Hu, Huan; Wan, Zehong; Jandu, Karamjit S.; Philps, Oliver J.; et al.
Graphical abstract: Abstract: We describe the discovery and optimization of 5-substituted-N-pyridazinylbenzamide derivatives as potent and selective LRRK2 inhibitors. Extensive SAR studies led to the identification of compounds18 and23, which demonstrated good in vitro pharmacokinetic profile and excellent selectivity over 140 other kinases. Both compounds demonstrated high unbound fractions in both blood and brain. Compound18 proved to be brain penetrant, and the high unbound fraction of compound18 in brain enabled its in vivo efficacy in CNS, wherein a significant inhibition of LRRK2 Ser935 phosphorylation was observed in rat brain following intravenous infusion at 5 mg/kg/h.